Efficacy of Rituximab in Patients with Autoimmune Bullous Disease: A Retrospective Cohort Study - Özge Aşkın; Ayşe Mine Gök; Tuğba Kevser Uzunçakmak; Zekayi Kutlubay (Van Tıp Dergisi, 2021)
INTRODUCTION: The aim of this study was to evaluate the effectiveness of rituximab in autoimmune bullous diseases. METHODS: In this study, the data of patients who received rituximab treatment for autoimmune bullous disease in our clinic between 2012 and 2019 were retrospectively reviewed. The patients age, sex, diagnosis, presence of cutaneous/mucosal involvement before infusion, number of infusions, anti-desmoglein 1, anti-desmoglein 3 and indirect immunofluorescence data before and after treatment, treatment responses and side effects were recorded. RESULTS: In our study, we found a significant decrease in anti-desmoglein 1 and anti-desmoglein 3 levels and accumulations in indirect immunofluorescence after rituximab treatment. (P <0.001 for both) DISCUSSION AND CONCLUSION: The results from our study showed that rituximab is an effective agent that can be used with systemic steroid treatment.